Toward a Functional Cure for HIV-1 Infection: The Block and Lock Therapeutic Approach - Vargas, Benni; Sluis-Cremer, Nicolas (Frontiers in Virology, 2022)
The persistence of latent, replication-competent HIV-1 proviruses in resting CD4+ T cells, and other cellular reservoirs, represents a major barrier to curing HIV-1 infection. Therapeutic approaches to eradicate these reservoirs include: (1) transplantation of hematopoietic stem cells engineered to lack the viral co-receptor CCR5; (2) gene editing to disrupt the HIV-1 genome; and (3) a “shock and kill” approach that reverses latency thus rendering the infected cells vulnerable to immune clearance mechanisms, including therapeutic or immunomodulatory enhancement strategies. There are, however, limitations associated with each of these approaches, including scalability, the delivery of gene editing constructs to all reservoir cells in vivo, and difficulties associated with the reversal of HIV-1 latency in all, and not just a subset, of infected cells. As an alternative, the “block and lock” strategy involves long-term silencing of HIV-1 proviruses to prevent viral rebound following therapy cessation. This approach elicits a functional, rather than sterilizing, cure. This review article focuses on therapeutic approaches (i.e., small molecules, nucleic acids and recombinant proteins) that have been identified to block and, in some cases, lock HIV-1 in the latent state. We also touch on critical research that needs to be accomplished to advance this approach into humans.